Meningkatkan Motivasi Belajar Anak Berdasarkan Minat Melalui Program Kerja “Bimbelove” di Desa Nanjung RW 04 dan RW 09 - Fulqihayati, Nurathfal Nissa; Ayu, Dyah; Hernahadini, Nelis (LPPPM STAI Darul Hikmah Bangkalan, 2024)
Tutoring is providing material and practical support to children in the field of education based on the child's learning needs and interests, so we strive to solve the urgency of education through the Real Work Lecture work program. The purpose of having tutoring or what we call